2017
DOI: 10.1016/j.bbi.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Skin colour changes during experimentally-induced sickness

Abstract: Skin colour may be an important cue to detect sickness in humans but how skin colour changes with acute sickness is currently unknown. To determine possible colour changes, 22 healthy Caucasian participants were injected twice, once with lipopolysaccharide (LPS, at a dose of 2ng/kg body weight) and once with placebo (saline), in a randomised cross-over design study. Skin colour across 3 arm and 3 face locations was recorded spectrophotometrically over a period of 8h in terms of lightness (L), redness (a) and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…We further predicted that sickness cues compared with healthy ones would evoke enhanced blood oxygen level-dependent (BOLD) changes in the odor-perception network (piriform cortex, orbitofrontal cortex, and amygdala) and in the face-perception network (fusiform gyrus, inferior and superior frontal gyrus, and amygdala). This prediction was based on previous studies demonstrating sickness-driven changes in body odors (12) and facial appearance (23) and on several studies indicating salience-and threat-driven changes in the respective olfaction-(24) and vision-(25) processing networks.…”
Section: Significancementioning
confidence: 99%
“…We further predicted that sickness cues compared with healthy ones would evoke enhanced blood oxygen level-dependent (BOLD) changes in the odor-perception network (piriform cortex, orbitofrontal cortex, and amygdala) and in the face-perception network (fusiform gyrus, inferior and superior frontal gyrus, and amygdala). This prediction was based on previous studies demonstrating sickness-driven changes in body odors (12) and facial appearance (23) and on several studies indicating salience-and threat-driven changes in the respective olfaction-(24) and vision-(25) processing networks.…”
Section: Significancementioning
confidence: 99%
“…However, evidence that facial coloration is associated with measures of susceptibility to infectious diseases is equivocal Henderson et al, 2017;Phalane et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have indicated that yellower and redder skin is also more attractive in male faces [37,38]. Skin yellowness and redness are probably linked to health and attractiveness because these colour properties vary with current health [39].…”
Section: (I) Skin Colour: Blood Oxygenation and Carotenoidsmentioning
confidence: 99%